Carbon dioxide reforming of methane by catalytic-plasma reactor over cu/zn/î³-al2o3 - Nikoo, Maryam Khoshtinat (Penerbit UTM Press, 2011)
In the current study, the influence of input power for conversion of CH4 and CO2 into syngas was investigated in both Dielectric Barrier Discharge (DBD) plasma and catalytic-plasma cylindrical reactors. It was observed that for both reactors, higher input power favored fragmentation reactions rather than recombination of light intermediates into heavier hydrocarbons, thus improving H2 yield. Meanwhile, the presence of Cu/Zn/AlsO3 catalyst enhanced the H2 yield from 16.5% to 19.1%, while the H2/CO ratio remained almost constant near unity, thus indicating the suitable ratio for Fischer-Tropsch (FTS) processes.